The Influence of Omnichannel Marketing Strategy on Visit Intention with Fear of Missing Out (FoMO) as a Mediating Variable: A Study on Visitors of Jolotundo Glamping and Edupark Nganjuk - Nadiva Adista Yulia Putri; Raya Sulistyowati (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the effect of omnichannel marketing strategy on visit intention to Jolotundo Glamping & Edupark, with Fear of missing out (FoMO) as a mediating variable. Despite the increasing integration of digital channels by tourism destinations, the effectiveness of omnichannel strategies in driving actual visit intention remains complex, indicating a gap between multi-platform presence and psychological consumer triggers. This study addresses this gap by incorporating FoMO as a mediating mechanism within the tourism marketing context. A quantitative explanatory approach was employed using a survey of 250 respondents who are within the productive age range (17-45 years) and have interacted with Jolotundo's digital channels. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that omnichannel marketing strategy significantly influences both FoMO and visit intention. Fear of missing out (FoMO) also has a significant effect on visit intention and partially mediates the relationship between omnichannel marketing and visit intention. This study contributes to the tourism marketing literature by highlighting the mediating role of psychological urgency in strengthening the effectiveness of integrated digital strategies for modern travel destinations.